Novel immunotherapeutic proteins: immunoligand - Strom, Terry (Henry Stewart Talks, 2007)
Potential advantages of mAB, Challenges for mAB, Antibody based therapeutic proteins, Attributes of immunoligands, Creation of Ig-based fusion proteins, Non-cytolytic IL-2/Fc fusion protein, Vaccine trial design, Creation of cytolytic IL-15R antagonist fusion protein, Application of immunoligand: immunogen for mAB production, to stain the cognate ligand, to identify cell surface cognate ligands via immunoprecipitation, to create long lived proteins to test the function of the targeting ligand in vivo and to modulate immune responses, Challenges for immunoligands
Archived at 2019/06/13